Partial and general equilibrium impacts of trade digitalization using structural gravity model - Yann Duval; Chorthip Utoktham (Asia-Pacific Research and Training Network on Trade (ARTNeT), 2024)
The study estimates partial and general equilibrium impacts of trade digitalization on trade flows using data from the UN Trade Digitalization Index (TDI) 2024 and a structural gravity model. This approach, unlike earlier gravity model studies on the topic, allows for the derivation of both trade and welfare effects associated with trade digitalization. Estimated partial equilibrium effects suggest that a 10 percent increase in trade digitalization may increase trade flows by approximately 8 percent globally. Based on the gravity model estimates, a general equilibrium model is constructed. Counterfactual simulations are conducted to further assess the potential effects of various trade digitalization reforms, where countries in different world regions and globally are brought from their current state of implementation to a common level. The general equilibrium results indicate that global trade increases by nearly 5 percent when partial implementation of the trade digitalization measures included in the UN TDI is achieved. When full trade digitalization is implemented, trade rises by almost 13 percent. Real wages also increase by over 3 percent when trade digitalization measures included in the UN TDI are fully implemented. Concurrently, producer prices fall by nearly 4 percent globally under the full implementation scenario. While the size of impacts varies across regions, the direction of impacts is consistent across all regions, confirming that trade digitalization offers great opportunities in inducing trade, as well as in increasing wages and reducing costs for consumers. The Pacific Islands and Sub-Saharan Africa emerge as the top beneficiaries in terms of potential trade growth, suggesting that trade digitalization be prioritized as part of their sustainable development plans.
hdl:20.500.12870/7374
Keywords: D50; F13; O14; 330; trade digitalization; trade digitalization index; TDI; structural gravity; generalequilibrium